1999
DOI: 10.1094/mpmi.1999.12.11.951
|View full text |Cite
|
Sign up to set email alerts
|

The Plant-Growth-Promoting Rhizobacterium Paenibacillus polymyxa Induces Changes in Arabidopsis thaliana Gene Expression: A Possible Connection Between Biotic and Abiotic Stress Responses

Abstract: This paper addresses changes in plant gene expression induced by inoculation with plant-growth-promoting rhizobacteria (PGPR). A gnotobiotic system was established with Arabidopsis thaliana as model plant, and isolates of Paenibacillus polymyxa as PGPR. Subsequent challenge by either the pathogen Erwinia carotovora (biotic stress) or induction of drought (abiotic stress) indicated that inoculated plants were more resistant than control plants. With RNA differential display on parallel RNA preparations from P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
283
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 503 publications
(295 citation statements)
references
References 38 publications
8
283
0
4
Order By: Relevance
“…Thus, in these Arabidopsis plants, resistance-inducing PGPR induced defence reactions commonly associated with pathogen infection. Similar results were obtained by Timmusk and Wagner (1999), who concluded that the resistanceinducing strain Paenibacillus polymyxa B2 induced mild biotic stress. These authors used gnotobioticallyraised plants on a nutrient medium, and by applying RNA differential display and real-time PCR, found six and an additional four genes, respectively, to be upregulated in response to the PGPR, including PR-1 and the drought-responsive gene ERD15.…”
Section: Expression Of Systemically Induced Resistance In the Plantsupporting
confidence: 86%
“…Thus, in these Arabidopsis plants, resistance-inducing PGPR induced defence reactions commonly associated with pathogen infection. Similar results were obtained by Timmusk and Wagner (1999), who concluded that the resistanceinducing strain Paenibacillus polymyxa B2 induced mild biotic stress. These authors used gnotobioticallyraised plants on a nutrient medium, and by applying RNA differential display and real-time PCR, found six and an additional four genes, respectively, to be upregulated in response to the PGPR, including PR-1 and the drought-responsive gene ERD15.…”
Section: Expression Of Systemically Induced Resistance In the Plantsupporting
confidence: 86%
“…In addition, insecticidal activities were reported for some PGPB in addition to the existing biocontrol repertoire with perspectives for application against insect crop pests [48]. Recent reports suggest that PGPB also enhance the tolerance of plants towards abiotic stresses such as drought [54,58], chilling injury [3], salinity [22], metal toxicity [13] and elevated temperature stress [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…IST against drought or salt stresses in plants can be induced with systemic application of certain rhizobacteria including Grampositive Bacillus strains (Ryu et al, 2004;Timmusk and Wagner 1999;Zhang et al, 2010), an endophytic fungal isolate, Trichoderma harziarum (Bae et al, 2010), and certain Gram-negative bacterial isolates, such as ACCdeaminase producing bacteria (Mayak et al, 2004). Root colonization by Pseudomonas chlororaphis O6 induced systemic resistance against a broad spectrum of plant diseases caused by viral, bacterial, and fungal pathogens in various plants by jasmonic acid-ethylene related pathways (Cho et al, 2008;Kim et al, 2004;Ryu et al, 2007;Spencer et al, 2003).…”
mentioning
confidence: 99%